Impact of individualized and structured aerobic exercise on clinical outcomes in pediatric congenital heart diseases with post-surgical rehabilitation: a meta-analysis - Awosika, Ayoola; Patel, Tirath; Rath, Shree; Henna, Fathimathul; Alam, Umama; Ali, Aizaz; Adeniyi, Mayowa Jeremiah (Frontiers in Surgery, 2025)
BackgroundChildren with congenital heart defects (CHD) commonly experience decreased exercise capacity due to structural heart abnormalities, surgical interventions, and parental-and physician-imposed activity restrictions. This reduced activity can lead to physical deconditioning, impaired quality of life, and increased cardiovascular risk later in life. While exercise-based rehabilitation is highly recommended, significant knowledge gaps persist regarding the long-term impact of structured exercise on diverse CHD subtypes, optimal modalities, and standardized protocols for implementation. This meta-analysis assesses the effect of structured exercise rehabilitation programs on functional and health-related outcomes in children with CHD.MethodsA comprehensive search was done using PubMed/MEDLINE, Embase, and Web of Science until April 23, 2025, for randomized controlled trials (RCTs) and observational studies which compares exercise or cardiac rehabilitation with standard of care or no rehabilitation intervention in pediatric CHD patients. Key outcomes included changes in exercise duration, peak oxygen uptake (peak VO2), peak workload, heart rate, and other cardiopulmonary parameters. Data were analyzed and pooled using random-effects models, with heterogeneity evaluated via I2 statistics. Risk of bias (RoB) was assessed using RoB 2 for RCTs and ROBINS-I for observational studies, and evidence certainty was assessed using the GRADE approach.ResultsTen studies (5 RCTs, 5 observational) comprising of 378 patients were included. Exercise rehabilitation significantly elevated exercise duration [MD = 0.55, 95% CI: (0.01, 1.09); p = 0.04; I2 = 0%]. No significant advancement was seen in peak VO2 [MD = 1.14, 95% CI: (−1.07, 3.34); p = 0.31; I2 = 69%], peak workload, heart rate, or other cardiopulmonary parameters. Heterogeneity was high for several outcomes, especially peak workload and VO2, which was settled in sensitivity analyses for specific subgroups. Evidence certainty was moderate due to heterogeneity and study limitations.ConclusionExercise rehabilitation moderately enhances exercise duration in pediatric CHD patients but does not notably enhance most cardiopulmonary parameters. High heterogeneity reflects outcomes variability by CHD subtype and intervention protocol. Standardized, multicenter trials are required to improve and optimise exercise prescriptions and evaluate long-term benefits.